Low cost carriers and the changing fortunes of airports in the UK. (December 2016) - Halpern, N.; Graham, A.; Dennis, N.
Abstract: This paper investigates how low cost carrier (LCC) developments have affected the traffic and financial performance of UK airports from 2002 to 2014. Considerable growth in traffic was experienced from 2002 to 2007, especially at regional airports as a result of LCC expansion. This was replaced with a more volatile period from 2008 to 2014 where many of the regional airports that experienced the greatest increases in traffic during the early years, then experienced the largest reductions. This has clearly had an impact on their financial well-being, resulting in reduced profits for many airports. It has also meant that many regional airports that seemed like attractive investments as a result of LCC expansion are now less financially appealing, especially given that the LCC sector in the UK appears to be shifting capacity to larger regional airports, and in some cases, London airports.